EVALUATION OF CIPPO MODEL PROGRAM IN ELDERLY EMPOWERMENT - Muhammad Irfan Hilmi (IKIP Siliwangi Bandung, 2022)
This study aims to evaluate the program on empowering the elderly community held at the Rumah Belajar. Evaluation of the implementation of the elderly community empowerment program using the CIPPO model (Context, Input, Process, Product, and Outcome). The CIPPO model is derived from the CIPP model which adds an Outcome aspect to measure the implementation of the product. This study uses a qualitative approach with a descriptive method. The research informants were 3 informants, managers, facilitators and elderly at the Rumah Belajar in Cihideung Village, West Bandung Regency. The data collection technique used in this evaluation is adjusted to the needs of data collection. as for the technique is observation, interview, study documentation. Data analysis using the Miles and Huberman model by means of data reduction, data presentation and drawing conclusions. The results of the study, based on the evaluation of the CIPPO model, it was found that the implementation of the elderly community empowerment program was in accordance with the planned objectives, the management had gone well, in general the activities were according to plan, the program results from the cognitive, affective and psychomotor aspects could be categorized as good and the impact able to maintain the independence of the elderly in the aspects of biological, psychological, social and spiritual needs.